Buku Ajar Berbantuan Model Pembelajaran Everyone is A Teacher Here: Upaya Meningkatkan Keterampilan Dasar Mengajar Calon Guru Biologi - Sadikin, Ali; Hakim, Nasrul (Department of Biology Education, Universitas Pendidikan Indonesia, 2019)
This research is a classroom action research, which aims to improve the teaching skills of students of biology education. The study consisted of two cycles each consisting of three meetings. To measure basic skills, an observation sheet was used which was used from a peer teaching assessment sheet developed by UPT PPL FKIP Jambi University. The results showed 65,2% of the basic facts included in the category enough. Percentage of teaching basic skills before the action of 65,2% included in the category enough. The percentage of basic learning scores increased in the first cycle to 70,6% included in the good category and in the second cycle increased to 77,1% included in the good category. Based on the research data it can be concluded that the learning textbook used by everyone's learning model is a teacher here who can improve the student basic teaching skills.